Perineal sensation: an important predictor of long-term outcome in open spina bifida. Issue 1 (30th August 2006) - Oakeshott, P; Hunt, G M; Whitaker, R H; Kerry, S
Abstract : Objectives: To see if perineal sensation in infants with open spina bifida is associated with a better long-term outcome, particularly in terms of survival, renal-related deaths and incontinence. Methods: We conducted a prospective cohort study on a complete cohort of 117 consecutive patients with open spina bifida, whose backs were closed non-selectively at birth between 1963 and 1971. A meticulous neurological examination in infancy showed that 33 (28%) of them had perineal sensation, defined as intact sensation to pinprick in at least one dermatome on one side in the saddle area (S2–4). Data recorded within 48 h of birth and during six reviews between 1972 and 2002 were used. Details of deaths were obtained from medical records and from the Office of National Statistics. Results: By December 2005, 57% (67/117) of the cohort had died. There were 50 survivors with a mean age 38 years (range 35–41). More of those with perineal sensation survived than those without (23/33 v 27/84, p<0.001). This difference was mainly caused by 19 renal deaths in those lacking perineal sensation. Crucially there were no renal-related deaths in those with perineal sensation (0/33 v 19/84, p = 0.003). Among the survivors, those with perineal sensation were more likely than the remainder to be continent of urine and faeces (10/23 v 1/27, p<0.001 and 18/23 v 9/27, p = 0.002 respectively). They were also more likely to be able to walk at least 50 m (11/23 v 5/27, p = 0.027) and never to have had pressure sores (15/23 v 9/27, p = 0.025). Conclusions: A simple assessment of perineal sensation in infancy predicts long-term outcome in terms of survival, renal prognosis and incontinence in open spina bifida.